Preventing injuries among water polo players: A quantitative survey - de Castro-Maqueda, G.; Amar-Cantos, F. E. (Journal of Physical Education and Sport, 2019)
The aim of this study was to investigate the most frequent water polo injuries and players` perception regarding the current state of injury treatment and preventative programs. Problem of statement: In the field of aquatic sports and water polo, in particular, little has been done to examine the player`s perception regarding the injuries, health hazards, causes and ways of preventing these injuries. However, many researchers have conducted systemic reviews and theory-based studies on the same issues. These studies are inadequate and insufficient in solving the problems of injuries in the water polo matches. Therefore, there is need to conduct additional quantitative studies to supplement the theory-based and systemic review studies regarding injuries during water polo game and training sessions. This need necessitated the conduction of this study with the intent of examining the player`s perception regarding the levels of injuries, causes and prevention measures in water polo sports activities. Method: The study involved a quantitative study design with 487 water polo players in the sample. These participants were required to complete an online survey. Results: 98.4%, 87% and 56% of the respondents reported having had Shoulder pain, sunburns, and groin pain at one point in their water polo playing and training life. 52% of respondents said they had protective gears on at the time the injury occurred. 61.3%, 16.3%, and 8.7% said that the current preventative and treatment programs are satisfactory, inadequate and needed improvement respectively. Conclusion: The current water polo injury treatment and preventative measures and inadequate and needs improvement. These improvements should focus on regulating pool water temperature, enhancing the quality of protective gears and patient-centered care to victims of severe fractures and hypothermia.